El proyecto de yuca en Ecuador y necesidad de información para el desarrollo de una nueva forma de utilizar la yuca: El caso de camarones - Chavez E., N. (International Center for Tropical Agriculture, 1989)
Based on the cassava agroindustrial model developed by CIAT, a similar cassava project was established in Manabi Province, Ecuador. Different methods and techniques were used to collect the information required to diagnose the local situation, from producers, merchants, consumers, industrialists, technicians, and specialists. Secondary sources of information were consulted to obtain statistical data; informal interviews were conducted with farmers to determine farm type and size as well as cultural practices. A socioeconomic characterization of on-farm production systems of cassava and associated crops was also made. Four visits were carried out at 3-mo. intervals, each with specific objectives. Since more precise data are required on the real production and demand for fresh cassava for human consumption and of raw material for the shrimp and poultry industries and other industrial purposes, a marketing study will be conducted covering consumers, retailers, wholesalers, and industries. The 10 farmers' associations in the province formed a union, gross profits being distributed among both members and nonmembers. New jobs have also been created. Estimates are given of the demand for CM and CF for the poultry and shrimp sectors, resp., for 1988. Perspectives, especially for the latter, are excellent. (CIAT)